The sutural and dentoskeletal effects of alternate expansion and constriction of deficient maxilla in young adults: a randomized controlled clinical trial - Amira Allam; Maha Mostafa; Basaruddin Ahmad; Ahmed Salama; Norma Ab Rahman (BMC Oral Health)
Abstract Background In adults, mini-screw-assisted rapid palatal expansion (MARPE) has proven to be an efficient method for overcoming the drawbacks of conventional expansion methods. In treating adult patients with anteroposterior deficient maxilla, the clinician had to decide between an intrusive surgical approach or a camouflage therapy to mask the Class III malocclusion. However, alternate rapid maxillary expansion and constriction (ALT-RAMEC) is the treatment of choice in younger patients. Methods The 7-week ALT-RAMEC protocol was modified and combined with MARPE to evaluate its efficiency and its sutural and dentoskeletal advantages over conventional MARPE in young adults. Twenty-nine patients with transverse and anteroposterior maxillary deficiency (mean age of 21.3) were randomly assigned to two groups. The conventional group received MARPE with its conventional expansion rate (Control group), while the ALT-RAMEC group was treated with a combination of MARPE and the ALT-RAMEC modified protocol. The efficiency of expansion, circummaxillary sutural displacement, and dentoskeletal effects were assessed. Analysis of the change before and after intervention was examined using paired t-tests while analysis of the parameters comparing the two groups was examined using an independent t-test. For variables that were not normally distributed, the p-value was obtained from Bootstrap for pairwise comparison (BCA). Results The two techniques showed 100% efficiency in producing expansion in both groups. Mid-palatal, frontonasal, and intermaxillary sutures were displaced and increased significantly in width after treatment with both protocols (p ≤ 0.001), while the zygomaticomaxillary sutures compressed and showed a significant decrease in width with conventional MARPE, though, expanded and increased significantly in width with the ALT-RAMEC group (p < 0.001). The dentoskeletal effects revealed that conventional MARPE produced a buccal molar tipping while ALT-RAMEC showed a more bodily movement of the anchor molars. Conclusion The modified ALT-RAMEC technique is a promising protocol sufficient to expand the maxilla transversely without tipping the anchored teeth in young adult patients. The successful subluxation of circummaxillary sutures might be a sign of hope for maxillary anteroposterior deficient patients if proven to aid in non-surgical maxillary protraction. Trial registration The study protocol was registered in ClinicalTrials.gov public website under the name “New Maxillary Expansion Technique in Adults” with identifier number “NCT04908540”, and registration dates: 25-05-2021 (First submitted) and 01-06-2021 (First posted).